Characterization of anthocyanins, phenolics, and flavonoids in a global carrot collection through application of chemometrics and FT-NIR spectroscopy - Seth, Romit; Fiecke, Chelsey; Guoying, Ma; Perkins-Veazie, Penelope; Cavagnaro, Pablo; Ferruzzi, Mario G.; Iorizzo, Massimo (Elsevier, 2025)
Purple carrot is an important source of anthocyanins as a natural food dye, yet research advancements in selecting purple cultivars with improved anthocyanin extractable yield and stability remain limited. This study used a large set of purple carrot accessions to characterize anthocyanins, phenolics, and flavonoids, their relationship to tissue-specific accumulation, extraction efficiency, color density, and color stability. A Fourier-transform near-infrared (FT-NIR) spectroscopy method was also developed to evaluate these metabolites. Fully purple roots showed the highest anthocyanin content and extraction efficiency. Non-acylated anthocyanin Cy3XG was identified as a limiting step in the biosynthesis of stable acylated anthocyanins. The sinapoyl-containing glycoside Cy3XSGG was the primary contributor to color density. Ten FT-NIR prediction models were developed to evaluate anthocyanins, chlorogenic, and caffeic acids. These findings support the selection of purple carrot with stable and uniform anthocyanin production and perform quality control in the natural colorant industry.